CARDIAC SURGERYEarly experience with implantation of the new biological Trifecta valve - Smoczyński, Radosław; Sarnowski, Wojciech; Kłapyta, Adrian; Szafron, Bartłomiej; Kosior, Dariusz; Sypuła, Sławomir; Drobiński, Dominik; Kaliciński, Zygmunt; Witkowska, Anna; Suwalski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction: Aortic stenosis (AS) is the most common valvular disease in Europe and the USA, and the second indication for cardiac surgery. The effective treatment of AS is based mainly on surgical valve replacement using either a mechanical or a biological prosthesis. This study describes the early experience with the new biological valve Trifecta (St. Jude Medical, Inc.). Material and methods: The study included 38 elective patients who underwent aortic valve replacement (AVR) or AVR with concomitant procedures. Pre- and postoperative comorbidities/complications, blood samples and echo were collected. Before discharge from the hospital all patients had vitamin K antagonist therapy for three months after the operation. Results : In all patients with AVR (19 patients) or AVR plus ascending aorta replacement (3 patients) or AVR plus non-coronary sinus plasty and ascending aorta replacement (1 patient) or Bentall de Bono self-made conduit procedures (1 patient) minimally invasive technique was used. Trifecta valves were successfully implanted in all patients, including in AVR with combined procedures (14 patients). Mean overall postoperative transvalvular gradient was 13 mm Hg in small roots (valve size 19 and 21 mm). Valve size 23 mm or more had single digit mean gradients. Total mortality rate was 5.2% (2 patients), and occurred among high-risk patients undergoing combined procedures. Conclusions: AVR using Trifecta is feasible and safe. Low postoperative mean gradients, especially in small roots (valve size 19 and 21 mm), are encouraging. Further investigations are necessary to confirm potential durability and positive impact on myocardial mass regression.